A Different Story - Seduction, Conquest and Discovery - Finn Janning (Copenhagen Business School (CBS), 2005)
There is a story about two companies, and how the one was supported and dominated by the other. Even today, more than 13 years after their separation, the support and domination of one company over the other seems to continue. In 2001 NNE (Novo Nordisk Engineering A/S), celebrated its tenth anniversary as an independent affiliate within the Novo Group. The anniversary was celebrated with a huge party at the Øksnehallen Exhibition Centre located in Copenhagen, Denmark. Here NNE launched its new Corporate Visual Identity (CVI). The CVI was created in order for NNE to show the world that it strived to become the market leader in the growing fields of biotechnology and pharmaceuticals. Equally important, NNE wanted to detach itself from its supporter and dominator, the company Novo Nordisk A/S. To begin with, NNE changed its name from Novo Nordisk Engineering A/S to NNE; secondly it created a new logo; and last, as a brand promise, it stated: Unique Know How. In fact, NNE changed all of its visual identity (i.e. CVI) in a manner like that of pirates who want to change identity by raising another flag on the mast before anchoring at a harbor.
hdl:10398/7128
Keywords: 650